1998
DOI: 10.1002/(sici)1098-2744(199812)23:4<217::aid-mc4>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of keratinocyte growth factor expression in human endometrium: Implications for hormonal carcinogenesis

Abstract: Estrogen is thought to be an important etiologic agent in endometrial and breast cancers. However, the mechanism or mechanisms by which estrogen acts as a hormonal carcinogen are not well understood. We hypothesize that in response to chronic exposure to estrogens, human endometrial stromal fibroblasts (ESF) produce factors that facilitate neoplastic transformation in epithelial cells. To test this hypothesis, we assessed the regulation of keratinocyte growth factor (KGF) mRNA and protein in ESF by interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…IL-1 was included in this study because previous nuclear run-on and promoter studies on the FGF7 gene indicated that IL-1 can stimulate FGF7 gene transcription , Finch et al 1995b. Moreover, previous studies have demonstrated that IL-1 can induce stromal cells to secrete FGF7 in cornea, skin and endometrium , Finch et al 1995b, Li & Tseng 1997, Weng et al 1997, Li & Rinehart 1998. These findings suggest that IL-1 could also have a role in inducing FGF7 production in breast stromal cells.…”
Section: Characterisation Of Fgf7 Release From Normal Breast Fibroblastssupporting
confidence: 70%
“…IL-1 was included in this study because previous nuclear run-on and promoter studies on the FGF7 gene indicated that IL-1 can stimulate FGF7 gene transcription , Finch et al 1995b. Moreover, previous studies have demonstrated that IL-1 can induce stromal cells to secrete FGF7 in cornea, skin and endometrium , Finch et al 1995b, Li & Tseng 1997, Weng et al 1997, Li & Rinehart 1998. These findings suggest that IL-1 could also have a role in inducing FGF7 production in breast stromal cells.…”
Section: Characterisation Of Fgf7 Release From Normal Breast Fibroblastssupporting
confidence: 70%
“…In contrast, PDTC specifically inhibits NF-B activation by decreasing the release of the IB inhibitory unit from latent NF-B (42). The NF-B signaling pathway does play a role in LPS-mediated effects, and this same pathway is involved in IL-1 induction of KGF-1 expression (23,52,59). Collectively, these data, in conjunction with ours, suggest that LPS induction of KGF-1 expression is mediated through NF-B.…”
Section: Discussionsupporting
confidence: 47%
“…Examination of the hormonal regulation of KGF expression has shown that in primate endometrium KGF expression is activated by progesterone (Koji et al 1994, Matsui et al 1997, whereas in cultured human endometrial cells KGF expression could be significantly increased after long-term culture with the non-steroidal estrogen, diethylstilbestrol (Li & Rinehart 1998). Hormonal regulation of KGF expression has been studied in ovarian follicles where estrogen and human chorionic gonadotropin were found to stimulate KGF expression in cultured bovine theca cells (Parrott & Skinner 1998).…”
Section: Introductionmentioning
confidence: 99%